Some evidence of “smart” public procurement: solutions for smes in Italy - Albano, Gian Luigi; Zampino, Roberto (Piccola Impresa / Small Business, 2013)
Although it is widely recognized that public procurement may act as a “pull” mechanism for development and employment, serious concerns are constantly voiced as to the friendliness of public procurement processes towards small and medium enterprises (SMEs), arguably the most vital sector of the EU economy. In this paper, we will have a look at the concrete measures taken at the EU level to promote an increasing inclusion of SMEs in public procurement markets. We will then focus on the Italian experience and dwell on the results achieved since the creation of Consip S.p.A., the National Central Purchasing Body. In particular, data on transactions below the EU thresholds from the e-Marketplace managed by Consip will allow us to shed some light on the patterns of trade between public buyers and the different subgroups of firms in the class of SMEs.